SAT0053 Carotid Ultrasound is Useful for the Cardiovascular Risk Stratification of Patients with Rheumatoid Arthritis: Results of a Population-Based Study. (23rd January 2014) - Corrales, A.; González-Juanatey, C.; Peiró, M.; Blanco, R.; Llorca, J.; Calvo-Río, V.; Loricera, J.; Ortiz-SanJuán, F.; González-Gay, M.
Abstract : Background: Accelerated atherogenesis leading to increased incidence of cardiovascular (CV) mortality has been reported in patients with rheumatoid arthritis (RA). The search of tools that may identify high-risk RA patients who may benefit from active therapy to prevent CV events is of major importance. Objectives: To determine if the use of carotid ultrasonography (US) may improve the stratification of CV risk of patients with RA. Methods: A set of 370 consecutive patients without history of CV events was studied to assess carotid intima-media thickness (cIMT) and plaques. As previously proposed, CV risk was calculated according to the modified SCORE (mSCORE) for RA that was adapted by the application of a multiplier factor of 1.5 in those patients fulfilling ≥2 of 3 specific criteria. Results: The mean disease duration was9.8years, 250 (68%) had rheumatoid factor/anti-CCP positivity and 61 (17%) extra-articular manifestations. Forty-three were excluded because they had type 2 diabetes mellitus or severe chronic kidney disease. CV risk was categorized in the remaining 327 RA patients according to mSCORE: mild (96 cases; 29.3%), moderate (201; 61.5%) and high/very high risk (30; 9.2%). Only 5 patients were reclassified as having high/very high CV risk when the mSCORE was applied. Severe carotid US abnormalities (cIMT > 0.90 mm and/or plaques) were uncommon in patients with low mSCORE (13%). Nevertheless, in patients with moderate mSCORE severe carotid US abnormalities were observed in 63% of cases. Amodel that included a chart mSCORE risk ≥5% plus the presence of severe carotid US findings in patients with moderate mSCORE risk (≥1% and <5%) yielded high sensitivity for high/very high CV risk (93 [95% CI: 88- 96]). Conclusions: Carotid US assessment may be useful to establish the CV risk in RA, in particular in patients with moderate mSCORE. Acknowledgements: This study was supported by grants from "Fondo de Investigaciones Sanitarias" PI06/0024, PS09/00748 and PI12/00060 (Spain). This work was also partially supported by RETICS Program, RD08/0075 (RIER) from "Instituto de Salud Carlos III" (ISCIII) (Spain). Disclosure of Interest: None Declared